Nilai-nilai Sosial dalam Novel Negeri Senja Karya Seno Gumira Ajidarma - Fransisca S.O. Dedi; Sudarmaji Sudarmaji; Frieska Maryova Rachmasisca (LPPM STKIP PGRI Bandar Lampung, 2022)
The problems raised in this study are related to social values ​​in the novel Negeri Senja by Seno Gumira Ajidarma. The research study of social values ​​in the novel Negeri Senja by Seno Gumira Ajidarma includes intrinsic elements and social values ​​in the form of the value of affection, the value of responsibility and the value of harmony in life in the form of democracy and cooperation. The approach used in this research is the sociology of literature approach. This means that something that is displayed in the work that has been studied is the content of the literary work, the goals and the things implied in the literary work itself related to social problems. The results of the study show that the novel Negeri Senja by Seno Gumira Ajidarma contains intrinsic elements and contains many social values. Classification of social values is based on social values including the value of affection, the value of responsibility and the value of harmony in life.